SISTEM INFORMASI PENANGANAN PT.TELKOM AKSES UNTUK E-TIKET GANGGUAN PELANGGAN - Lilis Anggraini (Lembaga Pengembangan Kinerja Dosen, 2021)
In the telecommunications era, many companies often use office-based (online) work, starting from work reports, making work plans to making official minutes, also implemented with a system that is connected to the internet network. Of course the company PT. Telkom Access also makes official minutes online or connected to the internet network. PT. Telkom Access uses a lot of facilities in the form of Google Drive to help monitor disturbance tickets for the use of its employees, but this is not completely smooth, sometimes it is slow and cannot be accessed due to several things such as the internet network being interrupted, simultaneous access, and other constraints, so to access and monitoring occurs often there are obstacles. At PT.Telkom company Access to monitoring trouble tickets is very important because these tickets will be sent via the helpdesk to technicians, for technicians doing work in the field, this often occurs because access is only monitoring tickets via Google Drive and chat media such as telegram. When Google Drive (Cloud Storage) is being filtered by another unit, there are problems with monitoring the order. With the problems that occur, an information system is created which aims to assist the process of working on trouble tickets, data collection and monitoring of trouble tickets on a web-based basis. In achieving the desired goals based on the background above, a study was made with the title